Effect of phosphate status on the sorption and desorption properties of some soils of northern India - Barrow, N. J; Debnath, Abhijit (Plant and soil, 2014)
AIMS: Enormous quantities of phosphate have been applied to world soils, yet we know little about effects of phosphate status on sorption properties. METHODS: We measured sorption and desorption of phosphate on soils from fertilized tea plantations from northern India and compared them with unfertilized soils. We also incubated phosphate at high temperature with a previously unfertilized soil and measured the effects. RESULTS: Sorption of phosphate was less marked on soils of high phosphate status whether derived from inherent fertility or fertilizer application. This occurred because high phosphate status made the surface charge on the reacting surfaces more negative. Phosphate status also affected desorption. The higher the phosphate status, the smaller the difference between sorption and desorption curves. This occurred because on soils of high phosphate status the pathways by which adsorbed anions diffuse were saturated and the slow reaction that follows adsorption was stopped. CONCLUSIONS: When low-phosphate soils are first fertilized, it is necessary to supply more phosphate than is removed in produce. However, after long-term phosphate fertilization, it is sufficient to only replace phosphate lost in produce. We need to find how much phosphorus it takes to reach this state and how many of the world’s soils have already reached it.